2022
DOI: 10.3390/microorganisms10101894
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Campylobacter jejuni 11168H in Acanthamoebae castellanii Provides Mechanistic Insight into Host Pathogen Interactions

Abstract: Campylobacter jejuni is the leading cause of bacterial foodborne gastroenteritis worldwide but is rarely transferred between human hosts. Although a recognized microaerophile, the majority of C. jejuni are incapable of growing in an aerobic environment. The persistence and transmission of this pathogen outside its warm-blooded avian and mammalian hosts is poorly understood. Acanthamoebae species are predatory protists and form an important ecological niche with several bacterial species. Here, we investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 75 publications
1
17
0
Order By: Relevance
“… C. jejuni 11168H flagella mutants abolished uptake by A. castellanii [11]. Here, live-cell imaging revealed that the C.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… C. jejuni 11168H flagella mutants abolished uptake by A. castellanii [11]. Here, live-cell imaging revealed that the C.…”
Section: Resultsmentioning
confidence: 99%
“… C. jejuni aggregate on the surface of Acanthamoebae prior to phagocytosis [10, 11], although it is now apparent that this aggregation is not essential to induce a productive internalization given that phagocytosis of the ∆ flaB mutant was dramatically reduced. Interestingly, this aggregation phenomenon was also observed during Listeria monocytogenes interactions with Acanthamoeba and was termed ‘backpacking’ [18].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations